CORPORATE SOCIAL RESPONSIBILITY, SOCIAL CAPITAL AND SUSTAINABLE DEVELOPMENT: LESSONS FROM AN INDONESIAN PALM OIL COMPANY - Risa Bhinekawati (Masyarakat Indonesia, 2017)
This paper reveals that corporate social responsibility (CSR) programs of a large palm oil company can actually build social capital that contribute to sustainable development goals (SDGs). Using an exploratory qualitative case study, this study investigates why and how a company improves social, economic, and social conditions of communities surrounding its palm oil plantations through smallholder farmers empowerment and social capital  development, from 1992 to 2011. A case study of a sustainable palm oil company in Indonesia was chosen as an exemplary case study for theoretical or purposive sampling. Primary and secondary data from company documents, media records, interviews and observations were analysed to develop a theoretical model. The study finds that the CSR program is driven by company’s strategic intention to fulfill their business needs by solving the social and  environmental issues surrounding its palm oil plantations. Through smallholder farmers’ development program, the company builds social capital that improves social relationship, farmers’ capabilities, and farmers’ access to finance and market; so they are capable to act collectively with the company to achieve economic, social, and environmental performance for both the farmers and the company. This research has created linkages for previously disparate areas of academic enquiry by showing the actual interrelationships between CSR, social capital, corporate sustainability and SDGs.Keywords: Indonesia, Corporate social responsibility, Palm oil plantations, Smallholder farmers, Social capital, Sustainable Development Goals ABSTRAKTulisan ini menunjukkan bahwa program tanggung jawab sosial perusahaan (CSR) dari suatu perusahaan kelapa sawit dapat membangun modal sosial yang berkontribusi pada pencapaian sasaran pembangunan berkelanjutan (SDGs). Dengan menggunakan metode riset kualitatif dan studi kasus eksploratif, penelitian ini menyelidiki mengapa dan bagaimana suatu perusahaan memperbaiki kondisi sosial, ekonomi, dan lingkungan hidup melalui pemberdayaan petani kecil dan pembangunan modal sosial bagi masyarakat di sekitar perkebunan kelapa sawit sejak 1992 hingga 2011. Sebuah perusahaan kelapa sawit besar dipilih sebagai studi kasus berdasarkan pada kriteria “exemplary case study”. Penelitian ini membangun model teori berdasarkan pada analisis data primer dan sekunder yang didapat dari dokumen perusahaan, catatan media, wawancara dan observasi. Program CSR yang dilakukan perusahaan didorong oleh tujuan strategis untuk memenuhi kebutuhan bisnisnya dengan memecahkan masalah sosial dan lingkungan hidup di sekitar perkebunan. Melalui program pemberdayaan petani kecil, perusahaan membangun modal sosial melalui peningkatan hubungan baik, peningkatan kemampuan manajemen dan teknis, serta pemberian akses keuangan dan pasar bagi petani. Dengan demikian, petani dan perusahaan dapat bekerja sama untuk mencapai tujuan ekonomi, sosial, dan lingkungan hidup. Tulisan ini membangun model teori dengan menghubungkan konsep CSR, modal sosial, kesinambungan perusahaan, dan SDGs yang terhubung di penelitian sebelumnya.Kata kunci: Indonesia, modal sosial, perkebunan kelapa sawit, petani kelapa sawit, pembangunan berkelanjutan, tanggung jawab sosial perusahaan